Oncoplastic breast reconstruction: Patient selection and surgical techniques. Issue 8 (23rd March 2016) - Savalia, Nirav B.; Silverstein, Melvin J.
Abstract : Standard breast conserving techniques often fail to achieve the desired goal of tumor extirpation with adequate margins while preserving breast cosmesis. The emergence of oncoplastic breast reconstruction addresses these limitations and also allows breast conservation in women who would not have met traditional criteria. Using various volume displacing oncoplastic techniques, tumors can be successfully resected from any quadrant of the breast, while maintaining or improved breast cosmesis, diminishing post‐radiation deformities, and providing breast symmetry. J. Surg. Oncol. 2016;113:875–882 . © 2016 Wiley Periodicals, Inc.